1981
DOI: 10.1002/chin.198108219
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF SOME NEWER FORMAZANS AND TETRAZOLIUM SALTS AND THEIR EFFECT ON RANIKHET DISEASE VIRUS AND THE VACCINIA VIRUS

Abstract: Die Hydrazone (I) bzw. (IV) wurden mit Ary1diazonium‐Salzen (II) zu den Formazanen (III) bzw. (V) umgesetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The results revealed that the two compounds were found to exhibit significant activity 87% and 83%, respectively against the Ranikhet disease virus. However no activity against vaccinia virus could be observed [63] .…”
Section: Pharmacological Activitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The results revealed that the two compounds were found to exhibit significant activity 87% and 83%, respectively against the Ranikhet disease virus. However no activity against vaccinia virus could be observed [63] .…”
Section: Pharmacological Activitiesmentioning
confidence: 98%
“…Some formazans possess antiviral activity [62,63] . For example, 1-(o-Carboxyphenyl)-3-(3′.4′-dimethoxy-6′-nitrophenyl)-5-phenylformazan 12 ( Chart 8 ), which was prepared by coupling of benzenediazonium chloride with the corresponding aldehyde N-(2-carboxyphenyl)hydrazone, was reported to exhibit 100% protection against the Ranikhet disease virus [62] .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…coworkers are virus specific, and the compounds did not affect vaccinia virus (10,11). On the basis of these findings by Misra and coworkers, we decided to determine whether the use of tetrazolium dyes as medium additives has a suppressive effect upon bacteriophage plaque assay titers.…”
mentioning
confidence: 95%
“…More recently, published dye concentrations range from 300 (15) to 50 (1) ,ug/ml. During the same intervening time period, Misra and coworkers (10,11) discovered that some tetrazolium compounds, and some formazans, possess antiviral activity against Ranikhet disease virus (Newcastle disease virus). The antiviral effects noted by Misra and * Corresponding author.…”
mentioning
confidence: 99%